Evaluation of the Preventive Effect of Photobiomodulation on Orofacial Discomfort in Dental Procedures: A Randomized-Controlled, Crossover Study and Clinical Trial - Bitencourt, Greice De Brito; Motta, Lara Jansiski; Teixeira Da Silva, Daniela De Fátima; Turcio, Karina Helga Leal [UNESP]; Sfalcin, Ravana Angelini; Gomes, Adrielle Mendes De Paula; Mesquita-Ferrari, Raquel Agnelli; Fernandes, Kristianne Porta Santos; Júnior, Aldo Brugnera; Bussadori, Sandra Kalil (SAGE Publications, 2021)
Background: Orofacial pain has been a prevalent symptom in the worldwide population, which may cause restrictions in daily activities and, consequently, have a great impact on the well-being of affected individuals. Photobiomodulation using light sources, such as low-level laser or light emitting diodes, with different wavelengths, has been widely used in the last years, in addition to being a noninvasive, low-cost resource and reducing pain. Objective: This study aimed at evaluating the effect of photobiomodulation as a protocol treatment to prevent facial muscle discomfort after long-term clinical procedures. Methods: The volunteers were randomized and allocated as follows: laser (n = 16) and placebo (n = 16) groups, following a crossover study design. The laser parameters were as following: 786 nm wavelength, 9 J per point, and 100 mW power of 2.393 W/cm2 irradiance. The discomfort was induced by simulating a 50-min dental procedure (with bilateral mouth open), and the pain scale (assessed bilaterally), tiredness, and temperature measurement through thermography were used for analysis. Results: The results showed a significant lower pain and tiredness in the laser group. Also, the results showed a statistically significant valid temperature change between the groups at times: T1, T40, and T50. Conclusions: According to our results, photobiomodulation showed a positive effect on the face musculature in patients submitted to the treatments, reducing pain and improving the subjective perception of exertion.
Keywords: electromyography; orofacial pain; photobiomodulation therapy; thermography